Análise da administração de ômega-3 intra-articular no manejo da osteoartrite induzida em ratos - Prado, Luciane Dellazari da Silva do (2022)
Osteoarthritis is a chronic disease of a progressive nature, very prevalent in the elderly, mainly affecting the knee, which results in functional limitations, impacting the physical, social and psychological context, causing a reduction in the quality of life of the elderly. In this way, the present dissertation in production I, systematically researched the literature on biopsychosocial aspects in osteoarthritis patients, aiming to analyze the correlation of this disease in the elderly with biopsychosocial aspects, where in the results obtained, the relationship of knee osteoarthritis in the patients' lives and is correlated with anxiety, depression and functional limitation, impairing interpersonal relationships, affecting physical and mental conditions and generating disability due to chronic pain. Production II analyzed, in an experimental animal model, the effectiveness of intra-articular infiltration of omega-3 in osteoarthritis induced by sodium monoiodoacetate (MIA), under the parameters of pain, inflammation, function and evolution of osteoarthritis, and the same obtained approval by the Ethics Committee on the Use of Animals (CEUA) of the Universidade de Passo Fundo (UPF). We used 50 male albino Wistar rats, supplied by the vivarium of the Universidade de Passo Fundo, with 16 weeks of age, weighing between 250 and 300 grams, submitted to an intra-articular induction of osteoarthritis with sodium monoiodoacetate 2mg/50μL. The animals were divided into 5 groups of 10 animals, being the control group, the lesion, and the treatment groups (hyaluronic acid, corticosteroid and omega-3). The following behavioral data were analyzed: Splash Test, joint diameter measurement, in addition to biochemical tests such as: thiobarbituric acid reactive substances (TBARS), total leukocyte count in whole blood, Alpha-1 glycoprotein - AGP and C-reactive protein, polyphenols and SH group, plain radiography in anteroposterior view of the knees and histopathology of the knee. The data were submitted to the normality test using the D'Agostino Pearson test. For data with normal distribution, ANOVA with Tuckey's post test was used, for non-normal data, Kruskall Wallis was used followed by Dunn's post test. Results were expressed as mean ± standard deviation. Values considered significant with (p<0.05). In this study, the clinical characteristics evidenced by the disease, such as edema, behavior related to depression, can be highlighted, however, we did not observe a significant difference between the treatment groups. Thus, we conclude that this pathology has a negative impact on the physical and mental well-being of these elderly people, consequently on the quality of life, the need to carry out more studies with low-cost therapies.